Net Working Capital versus Net Owner's Equity Approaches to Computing Zakatable Amount - Mohamed H. El-Badawi (International Institute of Islamic Thought, 1992)
Introduction Zakah is a form of tax and alms mandated by Islam? The concepts underlying zakah are that the rich are responsible for the poor and the poor have the right to receive zakah. This does not imply that Islam is anticapitalist; in fact, Islam motivates the rich to invest funds so they will not be diminshed by paying zakah. Islam opposes idle savings, as it encourages the investment of funds for increased production, employment, and assistance to the poor.~ Zakah is ordained by the Qur'an, but its technical details are interpreted by the rules and jurisprudence of Islam. All economic entities maintain financial records of some kind and prepare financial statements according to generally accepted accounting standards. These records and statements are designed for different purposes and are not necessary for determining the amount of wealth subject to zakah. Many researchers have investigated the methods employed to determine the zakatable amount levied on trade assets ('Urud al tijarah). These methods may be summarized into two approaches: a) the net working capital approach and b) the owner's equity approach. This paper investigates the feasibility of using the net working capital approach (i.e., accounting principles) and the owner's net equity approach (i.e., the Saudi system) to determine the zakatable amount of trade assets. It will also show the relationship between the two approaches. This paper is divided into five sections: a) introducing the principles and conditions of zakah accounting for businesses; b) discussing the net working capital approach and how to determine the growing capital as the basis for ascertaining the &table amount by analyzing the elements of working capital and the financial transactions during the year; c) analyzing the owner's equity approach used in Saudi Arabia to determine the &table amount; d) applying both approaches to a numerical example; and e) contrasting the growing capital with the zakatable amount. Principles and Conditions of Trade Zakah ('Urud al Tijarah) There are two types of assets. The first type, which is not subject to zakah, includes those capital assets owned for the purpose of using them in one's business. Examples of such assets are the tools and machines used for production or marketing. The second type, which is subject to zakah, includes those assets manufactured or purchased for malung a profit by reselling them ...